Follicular Unit Excision Donor Area Management and Considerations of the Scalp - Carman, Timothy P.; Rassman, William (Facial Plastic Surgery, 2023)
Over the last several years, follicular unit excision (FUE) donor harvesting has become the predominant donor harvest method, surpassing the traditional method of linear strip excision donor harvesting. While this may offer advantages in specific clinical settings, the reality of ongoing losses with the natural evolution of male patterned hair loss places a premium on obtaining as much lifetime donor hair as possible to address this clinical reality. This lifetime demand requirement must be weighed against the possibility of a detrimental cosmetic appearance of the donor area with serial donor harvests utilizing FUE. This chapter will examine the important technical and artistic considerations critical for hair restoration surgeons to appreciate in order to maintain cosmetically high-quality donor area outcomes in patients choosing to undergo FUE harvesting for hair transplantation surgery.
Keywords: follicular unit excision; donor area outcomes; overharvesting; linear strip excision; artistic considerations; diffuse unpatterned alopecia; donor cosmesis